Legal Protection of Consumers and Sevensya Car Wash Marketing Strategy - Dwi Anindya Harimurti; Krisdayanti Simangunsong (LPPM Institut Studi Islam Sunan Doe, 2022)
Consumer protection is a form of protection in fulfilling consumer rights as a whole by service providers or business actors aimed at consumers with the aim that legal problems will not arise later after the process of cooperation between consumers and business actors has been carried out, especially in terms of marketing strategies regarding services. Sevensya car wash. The purpose of writing this journal is to study and understand how to protect consumers and the efforts made in marketing Sevensya's car wash services. Writing in this journal uses qualitative legal research methods by conducting research in the field and legislation. The results of the research that has been carried out can be concluded that Sevensya car wash services are responsible for fulfilling consumer rights if there is negligence by business actors which results in losses to consumers, and online marketing, they can use their social media such as Instagram, Facebook while offline usually done by distributing flyers.